Photovoltaic enhancement of Si solar cells by assembled carbon nanotubes - Zhang, Yafei; Wang, Yanfang; Chen, N.; Wang, Yanyan; Zhang, Yaozhong; Zhou, Zhihua; Wei, Liangming (Nano-Micro Letters, 2010)
Photovoltaic conversion was enhanced by directly assemble of a network of single-walled carbon nanotubes (SWNTs) onto the surface of n-p junction silicon solar cells. When the density of SWNTs increased from 50 to 400 tubes μm−2, an enhancement of 3.92% in energy conversion efficiency was typically obtained. The effect of the SWNTs network is proposed for trapping incident photons and assisting electronic transportation at the interface of silicon solar cells.